2021
DOI: 10.1101/2021.07.03.450982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PARP Inhibition Impedes the Maturation of Nascent DNA Strands During DNA Replication

Abstract: PARP1 is implicated in the detection and repair of unligated Okazaki fragment intermediates, highlighting these structures as a potential source of genome breakage induced by PARP inhibition. In agreement with this, we show here that PARP1 activity is greatly elevated in chicken and human S phase cells in which FEN1 nuclease is genetically deleted, and that PARP activity is highest tens of kilobases behind DNA replication forks. Importantly, PARP inhibitor reduces the integrity of nascent DNA strands in both w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…Since DNA2 is required for DSB repair, the enhancement of PARPi sensitivity by DNA2i has been ascribed to the putative selectivity of PARPi for the DSB repair phenotype of BRCA-deficient cells (Cong et al, 2021). However, PARP is also implicated in protecting from ssDNA damage (Cong et al, 2021; Hanzlikova et al, 2018; Vaitsiankova et al, 2022). Thus, over-resection at ssDNA damage may also contribute to DNA2i and PARPi synergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since DNA2 is required for DSB repair, the enhancement of PARPi sensitivity by DNA2i has been ascribed to the putative selectivity of PARPi for the DSB repair phenotype of BRCA-deficient cells (Cong et al, 2021). However, PARP is also implicated in protecting from ssDNA damage (Cong et al, 2021; Hanzlikova et al, 2018; Vaitsiankova et al, 2022). Thus, over-resection at ssDNA damage may also contribute to DNA2i and PARPi synergy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, over-resection at ssDNA damage may also contribute to DNA2i and PARPi synergy. Specifically, on the lagging strand, PARP regulates a back-up mechanism for defective Okazaki fragment processing that can lead to an accumulation of unreplicated gaps (Hanzlikova et al, 2018; Vaitsiankova et al, 2022), possibly involving downstream pol α-primase repriming (Kolinjivadi et al, 2017b). PARP has been demonstrated to be involved in protection from excessive DNA2-dependent degradation of nascent DNA on the lagging strand (Thakar et al, 2019; Thakar et al, 2020), implying a need for DNA2 in processing lagging strand restart intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…PARP1 localized to replication sites then recruits the SSB repair protein XRCC1, which facilitates DNA ligation of nicks by Lig3 [51]. PARP1 inhibition in FEN1-deleted DT40 chicken cells caused the mutant cells to accumulate additional ssDNA nicks and gaps [52]. A very recent study showed that DNA gaps in lagging-strand DNA caused by Pol δ blockade by G4 may be recognized by the 9-1-1 complex.…”
Section: Dna Damage Responses In Ofmmentioning
confidence: 99%
“…They have a heightened sensitivity to loss of the canonical flap endonuclease 1 (FEN1) that generates ligatable nicks (Cong et al, 2021;Guo et al, 2020;Mengwasser et al, 2019;Ward et al, 2017). Given that PARPi also hinders the maturation of nascent DNA strands during DNA replication (Vaitsiankova et al, 2022), these findings implicate that lagging strand synthesis is a vulnerability in BRCA-deficient cells underlying the cytotoxicity of PARPi.…”
Section: What Is the Source Of Gaps?mentioning
confidence: 99%